Grid Mapping Catheter for Ventricular Tachycardia Ablation. (September 2019) - Okubo, Kenji; Frontera, Antonio; Bisceglia, Caterina; Paglino, Gabriele; Radinovic, Andrea; Foppoli, Luca; Calore, Federico; Della Bella, Paolo
Abstract : Background: A new grid mapping catheter (GMC)—allowing for bipolar recordings of the electrograms in each orthogonal direction—became available. The aim of the current study is to evaluate the utility of the GMC in creating substrate and ventricular tachycardia (VT) activation maps during VT ablation procedures. Methods: From December 2017 to July 2018, 41 consecutive patients undergoing a VT ablation procedure using a GMC were studied. During the substrate mapping, 3 different maps were created using the 3 GMC bipolar configurations (along the spline, across the spline, HD wave solution); the low voltage area and late potential areas were compared. In case of inducible VTs, the GMC was used to create the VT activation maps focusing on the diastolic interval. The relation between diastolic activities during VT and substrate abnormality during sinus rhythm was also investigated. Results: The median low-voltage area drawn by the HD wave configuration was 28.9 cm 2, 13% and 15% smaller than the low-voltage areas identified by the along and across configuration, respectively (33.1 and 33.9 cm 2 ; P <0.0001). The late potential areas obtained with the 3 GMC configuration did not differ ( P >0.05). VT activation mappings using the GMC were performed in 40 VTs, visualizing the full diastolic pathway in 22 (55%) of them. While the latest late potential areas were included in VT diastolic pathway in 17 VTs, the other 6 VTs showed mismatching of them. Identifying the full diastolic pathway led to a higher ongoing VT termination rate during the ablation than in case of partial recordings (88% versus 45%; P =0.03); furthermore, in the former situation, the noninducibility of the targeted VTs was achieved in all cases. Conclusions: The GMC is a useful tool for performing substrate and VT activation mappings during the VT ablation procedure, precisely identifying the low-voltage areas and quickly visualizing the diastolic pathways.